PENGEMBANGAN PENUNTUN PRAKTIKUM KIMIA PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT KELAS X SMA - Dwi Intan Purnamasari; Husna Amalya Melati; Ira Lestari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
The research was aimed to know the feasibility and readability of the guidance of chemistry practical work that was developed in electrolite and non electrolite solution’s material. This research uses research & development (R & D) which adopted development model of Borg & Gall. The subject of this research is the guidance of chemistry practical work which the readability to the student of XI IPA 2 SMA Negeri 2 Sungai Raya is examined in the first readability test and to the students of XI IPA 1, 2, and 3 in the second readability test. The result of expert judgement shows that the guidance of chemistry practical work is really feasible to be used in learning process considered of the content, present, language, and graph feasibility are 82.40%; 84%; 91.11%; and 80%. Based on the calculation of  student response percentage to the guidance of chemistry practical work gained the result of  first readibility test is 82.62% and the second readability test is 80.04%. This shows that the readability of the guidance of chemistry practical work is categories very high. Keywords: Guidance of practical work, electrolite and non electrolite, feasibility, readability